Mechanism of calcitriol regulating parathyroid cells in secondary hyperparathyroidism - Zeli Xiang; Ming Wang; Changxiu Miao; Die Jin; Hongyue Wang (Frontiers Media S.A., 2022)
A common consequence of chronic renal disease is secondary hyperparathyroidism (SHPT) and is closely related to the mortality and morbidity of uremia patients. Secondary hyperparathyroidism (SHPT) is caused by excessive PTH production and release, as well as parathyroid enlargement. At present, the mechanism of cell proliferation in secondary hyperparathyroidism (SHPT) is not completely clear. Decreased expression of the vitamin D receptor (VDR) and calcium-sensing receptor (CaSR), and 1,25(OH)2D3 insufficiency all lead to a decrease in cell proliferation suppression, and activation of multiple pathways is also involved in cell proliferation in renal hyperparathyroidism. The interaction between the parathormone (PTH) and parathyroid hyperplasia and 1,25(OH)2D3 has received considerable attention. 1,25(OH)2D3 is commonly applied in the therapy of renal hyperparathyroidism. It regulates the production of parathormone (PTH) and parathyroid cell proliferation through transcription and post-transcription mechanisms. This article reviews the role of 1,25(OH)2D3 in parathyroid cells in secondary hyperparathyroidism and its current understanding and potential molecular mechanism.